Distinct phenotypic traits of Staphylococcus aureus are associated with persistent, contagious bovine intramammary infections. Issue 1 (December 2018) - Grunert, Tom; Stessl, Beatrix; Wolf, Franz; Sordelli, Daniel; Buzzola, Fernanda; Ehling-Schulz, Monika
Abstract Staphylococcus aureus causing persistent, recurrent bovine intramammary infections are still a major challenge to dairy farming. Generally, one or a few clonal lineages are predominant in dairy herds, indicating animal-to-animal transfers and the existence of distinct pathotypic traits. The aim of this study was to determine if long term persistence and spreading ofS. aureus are associated with specific phenotypic traits, including cellular invasion, cytotoxicity and biofilm formation. Mastitis isolates were collected over a 3-years period from a single dairy herd, resulting in two persistent subtypes, the high within-herd prevalent subtype ST9 (CC9)-methicillin-susceptibleS. aureus (MSSA), designated HP/ST9, and the low within-herd prevalent subtype ST504 (CC705)-MSSA, designated LP/ST504. Characterization of the two different coexisting persistent subtypes showed that the following phenotypic traits are particularly associated with high within-herd prevalence: lack of capsular polysaccharide expression, high cellular invasiveness, low cytotoxicity and high biofilm/ poly-N-acetylglucosamine (PNAG) production, which may concomitantly contribute to the spreading of HP/ST9 within the herd. By contrast to HP/ST9, LP/ST504 is characterized by the formation of colony dendrites, which may help the bacteria to access deeper tissues as niches for persistence in single animals. Thus, within a single herd, two different types of persistence can be found in parallel, allowing longtime persistence ofS. aureus in dairy cattle. Furthermore, this study indicates that ST9 (CC9)-MSSA strains, which are currently thought to have their primary reservoir in swine and humans, can also successfully spread to new hosts and persist in dairy herds for years.